Strain manipulation of magnetocaloric effect in a Ni39.5Co8.5Mn42Sn10 melt-spun ribbon. (February 2023) - Yang, Jiajing; Li, Zongbin; Yang, Bo; Yan, Haile; Cong, Daoyong; Zhao, Xiang; Zuo, Liang
Abstract: Heusler-type Ni-Mn-based alloys can demonstrate large magnetocaloric effect through magnetic field-induced phase transformation, but it usually occurs in a relatively narrow temperature region. In this work, we fabricate a bilayer composite with a Ni39.5 Co8.5 Mn42 Sn10 ribbon adhered to a Ni50 Ti50 substrate in order to manipulate the magnetocaloric properties by using the recovery strain of the predeformed substrate. The transformation temperatures of the ribbons can be effectively shifted to higher temperature region through the external strain transferred from the substrate, which contributes to the extended cooling temperature region. Moreover, the effective refrigeration capacity can also be improved by such strain manipulation. Graphical abstract: Image, graphical abstract